Implementasi Prinsip Hukum Internasional dalam Pengaturan Perdagangan Digital Global: Tantangan dan Implikasi terhadap Keadilan Ekonomi - Johanes Artnandhi Tejamaya; Ragil Barry Prastiyo; Dwi Imroatus Sholikah (IAI Nasional Laa Roiba Bogor, 2026)
Global digital trade has become a crucial pillar of modern economic growth; however, its rapid development presents new challenges for the international legal system. The lack of regulatory harmony among nations, technological disparities, and weak protection of economic justice highlight the need to strengthen international legal principles that are adaptive to the digital era. This study aims to analyze the application of international legal principles in regulating global digital trade and to examine their implications for economic justice among nations. The research employs a normative juridical method using statutory, conceptual, and comparative approaches by reviewing various international legal instruments such as the WTO Agreement on E-Commerce and the UNCITRAL Model Law on Electronic Commerce. The findings reveal that the implementation of principles of equality, non-discrimination, and economic justice remains limited due to political interests and disparities in legal capacity among countries. The discussion emphasizes the importance of reformulating international legal principles to accommodate the dynamics of digital trade in a fair and inclusive manner. This study concludes that international law must transform from a mere regulatory instrument into an ethical tool for promoting global economic justice through collaborative and sustainable digital governance.